Asymptotic Behavior of Ground State Radial Solutions for -Laplacian Problems - Sonia Ben Othman; Rym Chemmam; Habib Mâagli (Journal of Mathematics)
Let , we take up the existence, the uniqueness and the asymptotic behavior of a positive continuous solution to the following nonlinear problem in , , , , where , is a positive differentiable function in and is a positive continuous function in such that there exists satisfying for each in , , and such that .